THE EFFECTIVENESS OF ANGER MANAGEMENT ROOMS ON THE PSYCHOLOGICAL RECOVERY OF ADDICTIVE CLIENTS - Aribowo Abdurrahman (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Addiction is a complex issue that not only affects the individual but also their psychological well-being. Anger management has been identified as a crucial component in the rehabilitation process for individuals struggling with addiction. This study explores the efficacy of Anger Management Rooms as an intervention for individuals undergoing addiction rehabilitation at the BNN Batam Rehabilitation Center. Addiction, often accompanied by complex emotional issues including anger, presents significant challenges in the recovery process. The Anger Management Room offers a structured environment where individuals can learn and practice anger management techniques, such as cognitive-behavioral therapy, relaxation training, and emotional expression. By providing tools to identify, understand, and manage anger, this intervention aims to reduce relapse rates and improve overall well-being. This paper reviews existing literature to assess the effectiveness of Anger Management Rooms in addressing the emotional needs of individuals in recovery and discusses the various techniques employed within these spaces